BMSC-Derived Small Extracellular Vesicles Induce Cartilage Reconstruction of Temporomandibular Joint Osteoarthritis via Autotaxin–YAP Signaling Axis - Wang, Yingnan; Zhao, Miaomiao; Li, Wen; Yang, Yuzhi; Zhang, Zhenliang; Ma, Ruijie; Wu, Mengjie (Frontiers in Cell and Developmental Biology, 2021)
Background: Temporomandibular joint osteoarthritis (TMJOA) seriously affects the health of patients, and the current treatments are invasive and only used for advanced cases. BMSC-derived small extracellular vesicles (BMSC-sEVs) may represent a safer and more effective treatment, but their role in TMJOA has not been elucidated. This study attempted to analyze the cartilage reconstruction effect of BMSC-sEVs on TMJOA and the mechanism underlying this effect. Methods: BMSC-sEVs were isolated and purified by microfiltration and ultrafiltration and were subsequently characterized by nanoparticle tracking analysis, electron microscopy and immunoblotting. TMJOA models were established in vivo and in vitro and hematoxylin-eosin staining, immunohistochemistry and histological scoring were performed to analyze the histological changes in TMJOA cartilage tissues treated with BMSC-sEVs. The proliferation, migratory capacity and cell cycle distribution of TMJOA cartilage cells treated with BMSC-sEVs were detected. Furthermore, the related mechanisms were studied by bioinformatic analysis, immunoblotting and semi-quantitative PCR, and they were further analyzed by knockdown and inhibitor techniques. Results: The acquisition and identification of BMSC-sEVs were efficient and satisfactory. Compared with the osteoarthritis (OA) group, the condylar tissue of the OA group treated with BMSC-sEV (OAsEV) showed an increase in cartilage lacuna and hypertrophic cartilage cells in the deep area of the bone under the cartilage. Significantly upregulated expression of proliferating cell nucleoantigen and cartilage-forming factors and downregulated expression of cartilage inflammation-related factors in OAsEV were observed. In addition, we found higher rates of cell proliferation and migratory activity and alleviated G1 stagnation of the cell cycle of OAsEV. Autotaxin was found in the BMSC-sEVs, and key factors of the Hippo pathway, Yes-associated protein (YAP), p-YAP, etc. were upregulated in the OAsEV group. Treatment with BMSC-sEVs after autotaxin knockdown or inhibition no longer resulted in expression changes in cartilage-forming and inflammation-related factors and key factors of the Hippo pathway. Conclusions: These results suggest that the autotaxin-YAP signaling axis plays an important role in the mechanism by which BMSC-sEVs promote cartilage reconstruction in TMJOA, which may provide guidance regarding their therapeutic applications as early and minimally invasive therapies for TMJOA, and provide insight into the internal mechanisms of TMJOA.